Gochu Asturcelta semiextensive production: Carcass and meat quality and fatty acid profile - Vieira C.; Martínez B.; Fernández A.M.; Sánchez C.I.; Rubio B.; Menéndez J. (7th International Symposium on the Mediterranean Pig, 2012)
The breeders association of Gochu Asturcelta (ACGA), has recovered Asturcelta pig breed. The aim of this work is to characterize the carcass and meat produced. Sixteen carcasses were used and carcass weight, dressing percentage and fatness were assessed. Likewise, meat quality parameters as pH, colour (L*, a*, b*), proximal chemical composition, fatty acid profile, water holding capacity, instrumental texture (Warner-Braztler) and sensory analysis were performed. Average carcass weight and dressing percentage were 180 ± 30 kg and 79 ± 3% respectively. Thickness subcutaneous fat was higher than common modern breeds (44 ± 9 mm 6th and 54 ± 6 mm gluteus medius). Meat colour measurements revealed lower L* and higher a* values than common commercial breeds. Chemical composition revealed a high intramuscular fat content (9.2 ± 3.5%FM), but fatty acid profile showed a higher content in MUFA than common modern breeds. Water holding capacity was higher than commercial hybrids. Instrumental texture and sensory analysis show that this meat could be defined as tender, juicy and with good palatability.
7. International Symposium on the Mediterranean Pig, 2010/10/14-16, Córdoba (Spain)